Adaptation of Douce Apocalypse Manuscript Illustration in Esti From Short Animation “Maaf Dari Esti” - Stella Natania; Christian Aditya (Universitas Multimedia Nusantara, 2017)
Forced Eviction is one of issues that keep on lingering around our society. The victim of this event usually doesn’t have much option to choose or fight over. Based on this issue and a short story about the same issue, “Maaf dari Esti” was created. The story will be visualized with gothic style to picture the quirk and sadness, not only the environtment but aso the character. Esti,the protagonist of the story will be designed according to Douce Apocalypse Illustration without abandon the three dimention base of the character. Keywords: forced eviction, gothic, three dimension